KARAKTERISTIK INDIVIDU, KEMAMPUAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Udik Jatmiko; Indah Yuni Astuti (Universitas Islam Kadiri, 2021)
The problem that is the focus of the research discusses human resource management regarding individual characteristics, abilities and work environment that affect the performance of employees at UD Berkah Mandiri. Population of 89 respondents. The data analysis technique used in this study was the instrument validity and reliability test, multiple linear regression test, classical assumption test and hypothesis test through the t test and F test. The results obtained significant values. t of 0.000 <0.05 means that there is a partial influence between individual character (X1) on employee performance. Significant value. t is 0.001 <0.05, which means that there is a partial influence between the work ability variable (X2) on employee performance. Significant value. t is 0.005 <0.05, which means that there is a partial influence between work environment variables (X3) on employee performance. significant value of F of 0.000 <sig. 0.05. Based on these calculations, it can be explained that Ha is accepted and Ho is rejected. It can be explained that the influence of individual characteristics (X1), work ability (X2) and work environment (X3) on employee performance at UD Berkah Mandiri.